What is meant by land-use change? Effects of mining activities on forest and climate change - Gencay, Gokce; Durkaya, Birsen; Gençay, Gökçe; Durkaya, Birsen (Springer, 2023)
The ownership of 99.9% of forests in Turkey belongs to the State. According to the mandatory provisions of the Turkish Constitution of 1982, the ownership of State forests cannot be transferred to third parties. However, forest legislation permits several activities within the State forests, other than forestry, under certain conditions. Thus, in this study, the legal process of mining permits granted in State forests in Turkey was analyzed, and the policies implemented in mining permits were tried to be evaluated. Then, how mining activities affect forestlands and the environment has been compared by taking international studies in the literature into account. The change in the amount of carbon stored in the forests where the land use changed as a result of the given mining permit was calculated using the biomass expansion factor (BEF) method. After the mining permit was granted, 53% of the land-use change occurred in the sample area, and there was a 43% decrease in the amount of carbon stored. According to the results of the analysis, before the mining permit was granted, the amount of carbon stored by the area in 2009 was calculated as 4400.23 tons. However, with the start of mining activities in 2011, nearly half of the trees in the area were cut down, which was caused this value to drop to 1911.12 tons. As a result of the mining activities that continued after this date, it was determined by 2021 that all the trees in the area were cut down, and the amount of carbon stored in the area decreased to zero.
Keywords: Forest; Climate Change; Mining; Permit; Carbon